2009
DOI: 10.1002/hbm.20809
|View full text |Cite
|
Sign up to set email alerts
|

Thalamo‐frontal white matter alterations in chronic schizophrenia

Abstract: Diffusion tensor imaging (DTI) and fiber tractography are useful tools for reconstructing white matter tracts (WMT) in the brain. Previous tractography studies have sought to segment reconstructed WMT into anatomical structures using several approaches, but quantification has been limited to extracting mean values of diffusion indices. Delineating WMT in schizophrenia is of particular interest because schizophrenia has been hypothesized to be a disorder of disrupted connectivity, especially between frontal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 61 publications
(84 reference statements)
4
84
0
Order By: Relevance
“…In this small sample, we could not detect a difference in the average FA or mean diffusivity for the tract connecting the thalamus to the LPFC (Supplementary Table S6), however, more subtle local differences in diffusion properties may exist along the tract that were not detected in the analysis of average values (Oh et al, 2009).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this small sample, we could not detect a difference in the average FA or mean diffusivity for the tract connecting the thalamus to the LPFC (Supplementary Table S6), however, more subtle local differences in diffusion properties may exist along the tract that were not detected in the analysis of average values (Oh et al, 2009).…”
Section: Discussionmentioning
confidence: 78%
“…This is not the first study pointing to altered diffusion parameters in the thalamus or thalamocortical pathways. DTI findings supporting altered integrity of thalamocortical connectivity in schizophrenia include controversial alterations of fractional anisotropy in the anterior limb of the internal capsule (ALIC) Kubicki et al, 2005;Mamah et al, 2010;Sprooten et al, 2009;Sussmann et al, 2009;Zhang et al, 2010;Zhou et al, 2008, but see Ashtari et al, 2007;Kito et al, 2009;Kyriakopoulos et al, 2008;Szeszko et al, 2005;White et al, 2007 for negative findings in younger individuals and Beasley et al, 2009 for lack of evidence of myelin abnormalities post-mortem), of the tracts connecting to the LPFC (Kim et al, 2008;Oh et al, 2009) and altered FA (Hashimoto et al, 2009) or mean diffusivity in the thalamus itself (Agarwal et al, 2008;Rose et al, 2006;Spoletini et al, 2011). Kim et al (2007) have performed a similar DTI study, with an identical a-priori hypothesis, but found only differences in the thalamic CDR defined by connectivity to the orbitofrontal, parietal, and medial prefrontal cortices.…”
Section: Discussionmentioning
confidence: 99%
“…Several regions have been demonstrated to have decreased functional or structural connectivity in associative cortices (prefrontal, temporal and parietal) and the limbic system notably [87][88][89]. Beyond these specific features of brain "dysconnectivity", very recent studies have also demonstrated a disruption of the small-world network organization in these regions as well as in the whole brain associated with this disease [90].…”
Section: Schizophreniamentioning
confidence: 94%
“…Although some studies have found differences in measures of white matter integrity in schizophrenia (Oh et al, 2009;Rose et al, 2006), others have not (Foong et al, 2002;Steel et al, 2001). Our null finding may be a result of several factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that schizophrenia may be characterized by abnormal resting state connectivity (Welsh et al, 2010), structural white matter connectivity (Oh et al, 2009;Rose et al, 2006), and grey matter morphometry (Corradi-Dell'acqua et al, 2011;Ellison-Wright and Bullmore, 2010;Saze et al, 2007;Takahashi et al, 2004) measures. To better understand whether the decreased spTMS-evoked thalamic response in patients with schizophrenia may be related to such abnormalities, here we examine resting state fMRI and structural (white and grey matter) data from the same subjects who participated in the spTMS-fMRI study described above (Guller et al, 2012).…”
mentioning
confidence: 99%